Non-invasive diagnosis of retinoblastoma using cell-free DNA from aqueous humour. Issue 5 (11th February 2019) - Gerrish, Amy; Stone, Edward; Clokie, Samuel; Ainsworth, John R; Jenkinson, Helen; McCalla, Maureen; Hitchcott, Carol; Colmenero, Isabel; Allen, Stephanie; Parulekar, Manoj; Cole, Trevor
Abstract : Retinoblastoma is the most common eye malignancy in childhood caused by mutations in the RB1 gene. Both alleles of the RB1 gene must be mutated for tumour development. The initial RB1 mutation may be constitutional germline or somatic (originating in one retinal cell only). Distinguishing between these alternative mechanisms is crucial, with wider implications for management of the patient and family members. Bilateral retinoblastoma is nearly always due to a constitutional mutation; however, approximately 15% of unilateral cases also carry a germline mutation, and identifying these cases is important. This can be achieved by identifying both mutation types in tumour tissue and excluding their presence in blood. Modern eye-saving chemotherapy treatment (systemic, intra-arterial and intravitreal) has resulted in fewer enucleations. As a result, tumour tissue required to identify sporadic RB1 mutation(s) is not always available. Modern intravitreal chemotherapeutic techniques for retinoblastoma involve aspiration of aqueous humour (AH), providing a novel sample source for analysis. By analysing cell-free DNA present in the AH fluid of eyes affected with retinoblastoma, we have developed a screening test capable of detecting somatic RB1 mutations that is comparable to current tests on enucleated tumour tissue. The results obtained with fluid from enucleated eyes were concordant with tumour tissue in all 10 cases analysed. In addition, AH analysis from two patients undergoing intravitreal chemotherapy successfully identified somatic variants in both cases. Our findings suggest that AH fluid is a promising source of tumour-derived DNA in retinoblastoma for analysis.